2019
DOI: 10.1002/acn3.752
|View full text |Cite
|
Sign up to set email alerts
|

The pedunculopontine region and breathing in Parkinson's disease

Abstract: Objective Respiratory abnormalities such as upper airway obstruction are common in Parkinson's disease ( PD ) and are an important cause of mortality and morbidity. We tested the effect of pedunculopontine region ( PPN r) stimulation on respiratory maneuvers in human participants with PD , and separately recorded PPN r neural activity reflected in the local field potential ( LF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Furthermore, the coupling between neural activity and respiration may facilitate our understanding of brain disease. Hyam et al stimulated the pedunculopontine region (PPNr) and observed improvement in upper airway function in Parkinson’s patients ( Hyam et al, 2019 ). Loss of neurons in the preBötzinger complex was found to cause sleep-disordered breathing ( McKay et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the coupling between neural activity and respiration may facilitate our understanding of brain disease. Hyam et al stimulated the pedunculopontine region (PPNr) and observed improvement in upper airway function in Parkinson’s patients ( Hyam et al, 2019 ). Loss of neurons in the preBötzinger complex was found to cause sleep-disordered breathing ( McKay et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…They were implanted with 1.5 mm-spaced St. Jude Medical Infinity directional DBS electrodes (Abbott, Plano,TX) as part of a clinical trial examining autonomic and motor function in MSA (STAG-MSA NCT03593512). We have previously described our surgical approach and technique 29 . Electrode placement was clinically confirmed after implantation by the fusion of preoperative magnetic resonance imaging (MRI) and postoperative computed tomography (CT) scans.…”
Section: Participantsmentioning
confidence: 99%
“…A recent study has confirmed beneficial effects of low-frequency PPN-DBS on the upper airways function, also showing a significant correlation between the increase of oscillatory α-band activity and forced respiratory manoeuvres [85]; this effect was particularly marked when the rostral PPN was stimulated, as a part of the "mesencephalic locomotor region" (MLR); in animal studies, the MLR has been shown to project directly to a medullary respiratory generator and plays a key role in changes in respiration linked to motion [86].…”
Section: Deep Brain Stimulation and Respiratory Failurementioning
confidence: 74%